A highly efficient strategy for enhancing the adsorptive and magnetic capabilities of biochar using Fenton oxidation. (November 2020) - Xu, Shuang; Li, Jihui; Yin, Zhibing; Liu, Sen; Bian, Siyao; Zhang, Yucang
Graphical abstract: Highlights: Fenton oxidation was first applied for presice modification of biochar. Incorporating iron into biochar matrix through pyrolysis was of great importance. A considerable number of oxygen containing groups were introduced. Great increase of adsorption capability was obtained for Cr (VI) and MB. Fenton oxidation leaded to increase of saturation magnetization. Abstract: Fenton modification, involving iron-promoted pyrolysis followed by H2 O2 oxidation, was first employed to improve the adsorptive and magnetic capabilities of biochar. Modified biochars were prepared from rubber tree bark and coconut shell through iron-promoted pyrolysis and subsequent H2 O2 oxidation, and their adsorption behaviors toward Cr (VI) and MB were evaluated in aqueous solution. The modified biochars pyrolyzed at 300 and 400 ˚C displayed much higher adsorption capabilities than corresponding pristine biochars for Cr (VI) and MB, respectively, ascribing to introduction of COOH, CO and C–O groups by Fenton oxidation. More importantly, saturation magnetization could be enhanced by transforming nonmagnetic iron oxides into γ-Fe2 O3 through H2 O2 oxidation. The removal of Cr (VI) and MB could be primarily contributed to the adsorption of biochar matrix by reduction/hydrogen bonding/cation exchange/electrostatic interaction and hydrogen bonding/cation exchange/electrostatic interaction, respectively. This would provide a novel and efficient strategy for making highly adsorptive magnetic biochar.